The correlation between resilience and mental health of adolescents and young adults: a systematic review and meta-analysis - Luo, Shulai; Hu, Jiangtao; Zhang, Junshuai; Mei, Zhengyang; Tang, Zhongjian; Luo, Shi (Frontiers in Psychiatry, 2025)
BackgroundAdolescents and young adults (AYAs) aged 10–25 exhibit an increased prevalence of mental health disorders. Resilience has been well established as a positive factor in promoting and protecting mental health. This systematic review and meta-analysis aimed to quantify the correlation between resilience and mental health in AYAs by including relevant observational studies. Additionally, it explored potential moderators such as percentage of female participants, sample regions, and resilience measurements.MethodsA comprehensive search of the PubMed, Embase, Cochrane Library, Web of Science and Scopus databases was conducted until September 2024. CMA 3.0 software was used to perform meta-analysis, publication bias and sensitivity analysis of the included studies, and the moderating effect was verified by meta-analysis of variance (ANOVA).ResultNineteen studies involving a total of 17,746 participants were included, and the summary effect sizes from the random effect model showed that resilience among AYAs had a correlation coefficient of -0.391 with negative indicators of mental health (95% CI: - 0.469, - 0.308, p < 0.001), and a correlation coefficient of 0.499 with positive indicators of mental health (95% CI: 0.400, 0.586, p < 0.001). Additionally, sample regions and resilience measurements significantly moderated the correlation between resilience and positive indicators of mental health.ConclusionResilience in AYAs showed a moderately negative correlation with negative indicators of mental health and a moderately strong positive correlation with positive indicators of mental health. The findings strengthened the basis for future resilience research in AYAs aged 10–25, highlighting the potential of resilience to help mitigate the increasing mental health challenges faced by this population.